Expressing an RbcS Antisense Gene in Transgenic Flaveria bidentis Leads to an Increased Quantum Requirement for CO2 Fixed in Photosystems I and II. - Siebke, K. (1997)
It was previously shown with concurrent measurements of gas exchange and carbon isotope discrimination that the reduction of ribulose-1,5-bisphosphate carboxylase/oxygenase by an antisense gene construct in transgenic Flaveria bidentis (a C4 species) leads to reduced CO2 assimilation rates, increased bundle-sheath CO2 concentration, and leakiness (defined as the ratio of CO2 leakage to the rate of C4 acid decarboxylation; S. von Caemmerer, A. Millegate, G.D. Farquhar, R.T. Furbank [1997] Plant Physiol 113: 469-477). Increased leakiness in the transformants should result in an increased ATP requirement per mole of CO2 fixed and a change in the ATP-to-NADPH demand. To investigate this, we compared measurements of the quantum yield of photosystem I and II ([phi]PSI and [phi]PSII) with the quantum yield of CO2 fixation ([phi]CO2) in control and transgenic F. bidentis plants in various conditions. Both [phi]PSI/[phi]CO2 and [phi]PSII/[phi]CO2 increased with a decrease in ribulose-1,5-bisphosphate carboxylase/oxygenase content, confirming an increase in leakiness. In the wild type the ratio of [phi]PSI to [phi]PSII was constant at different irradiances but increased with irradiance in the transformants, suggesting that cyclic electron transport may be higher in the transformants. To evaluate the relative contribution of cyclic or linear electron transport to extra ATP generation, we developed a model that links leakiness, ATP/NADP requirements, and quantum yields. Despite some uncertainties in the light distribution between photosystem I and II, we conclude from the increase of [phi]PSII/[phi]CO2 in the transformants that cyclic electron transport is not solely responsible for ATP generation without NADPH production.